Widespread Eosinophilic Pustular Folliculitis in a Nonimmunocompromised Patient - Almodovar-Real, Ana (Med Princ Pract, 2014)
OBJECTIVE: We present a case of eosinophilic pustular folliculitis, a rare dermatosis which is often associated with HIV infection or internal malignancies. CLINICAL PRESENTATION AND INTERVENTION: We report the case of a 66-year-old man with a medical history of hypertension. Histopathological examination showed a dense follicular inflammatory infiltrate with abundant eosinophils. The clinical response to indomethacin was excellent with no recurrence during the follow-up. CONCLUSION: The patient responded well to indomethacin treatment.